The Impact of the Transformation of the Kołobrzeg Port on the Initiation of the Innovative Maritime Cluster of Central Pomerania: An In-depth Interviews - Dariusz KLOSKOWSKI; Weronika KOSEK (Communications of International Proceedings, 2023)
The article refers to one of the basic development directions of countries with high potential related to the implementation of maritime infrastructure in areas with high investment capacity. The selected research area, i.e. the South Baltic Sea of ​​Poland, fits into the research topic, mainly due to the existence of high development capacity of the maritime industry, which is not fully used. Additionally, the indicated area is a strategic element in the predictive approach of building a new transfer channel for goods to Southern European countries. The main subject of the study is the Kołobrzeg seaport, the transformation of which should be focused on a model variable, based on the theory of the creation of an economic growth pole, constituting the basis for initiating a maritime cluster in this area, conditioning the development of the Koszalin subregion and ultimately constituting an important nodal point on the map of Europe. Due to the limitations of literature associated with the elements of the transformation of ports of agricultural importance, the in-depth interview was used to demonstrate the need of building a new seaport in Kołobrzeg, which could constitute an important pole of economic growth in the region with great potential in the future with the simultaneous inhibition of the tourist function. Focusing the research on an expert approach allowed to eliminate the element of social sentiment and focus on the substance related to the need for infrastructure changes in the port of Kołobrzeg. Showing the advantages of building a new transshipment hub concentrates on creating a maritime cluster, which would constitute an important element in building the technological base of the region, with the simultaneous implementation of a research focus in the area under the influence of metropolitan cities.
Keywords: port of Kołobrzeg; maritime economy; maritime cluster.